Somnofluoroscopy, computed tomography, and cephalometry in the assessment of the airway in obstructive sleep apnoea. Issue 3 (March 1992) - Pepin, J L; Ferretti, G; Veale, D; Romand, P; Coulomb, M; Brambilla, C; Lévy, P A
Abstract : BACKGROUND: Assessments of the upper airways in patients with the obstructive sleep apnoea syndrome are usually carried out on awake patients who are upright. The dynamics of the airway in a patient who is asleep and lying down may be different. METHODS: Somnofluoroscopy, computed tomography of the upper airway, and cephalometry were carried out in 11 patients with the obstructive sleep apnoea syndrome (10 male; mean (SD) age 53 (10) years) to examine the airway while they were awake and asleep. RESULTS: At somnofluoroscopy 10 patients were in stage 2 sleep and only one in REM sleep. At least five obstructive events were visualised by lateral fluoroscopy in each patient. Imaging allowed observation of the dynamics of airway collapse, which began in the oropharynx in all cases, progressing to the hypopharynx in 10 cases and to the laryngopharynx in five. At fluoroscopy the soft palate was seen to hook up during airway occlusion in 10 patients, thereby increasing its cross sectional area. It was then sucked down into the hypopharynx. Somnofluoroscopic and cephalometric findings agreed, eight of the 10 patients with hypopharyngeal collapse shown by somnofluoroscopy having an inferiorly placed hyoid bone according to cephalometry (distance from the mandibular plane to the hyoid bone (MP-H distance) increased); the one patient with no hypopharyngeal collapse had a normal MP-H. By contrast, six of the 11 patients had a normal or supranormal hypopharyngeal cross sectional area of the airway on the computed tomogram. CONCLUSIONS: Somnofluoroscopy allows examination of the dynamics of airway closure in this disorder and shows the important role of the soft palate in acting as a plug in the oropharynx. Dynamic studies are required to determine the pattern of pharyngeal obstruction in obstructive sleep apnoea.